Greenhouse Gas Emission Reduction Strategies in the Transportation, Waste, and Domestic Sectors - Haryono Setiyo Huboyo; Nurandani Hardyanti; Isna Maulidya Durrotunnisa; Isnaini Haya Amani; Tarisa Farrelia Febriana (Universitas Diponegoro, 2024)
Population growth in Pekalongan City leads to increased community activities, which in turn raises Greenhouse Gas (GHG) emissions in the transportation, waste, and domestic sectors. This study aims to inventory and project GHG emissions, develop reduction strategies, and design regulations to mitigate these emissions. The method used to inventory GHG emissions from the transportation sector is based on Tier 1 and 2 approaches, while the waste and domestic sectors use the Intergovernmental Panel on Climate Change 2006 method with Tier 1 accuracy. The results of the inventory and projection show that GHG emissions in the transportation sector will reach 455.084 Gg CO2eq by 2032. Strategies to reduce these emissions include optimizing green open spaces (RTH), rejuvenating public transportation, and developing a Bus Rapid Transit (BRT) system, which collectively are expected to reduce emissions by 1.23%. In the waste sector, projected emissions amount to 27.88 Gg CO2eq. Planned strategies, such as increasing waste service coverage to the Degayu Landfill, optimizing waste facilities, and utilizing biogas, can reduce emissions by 15.85%. In the domestic sector, projected emissions are 27.97 Gg CO2eq, with the strategy of developing community-based livestock biogas expected to reduce emissions by 0.22%